A cocktail of synthetic stimulants found in a dietary supplement associated with serious adverse events. Issue 6 (6th May 2014) - Venhuis, Bastiaan; Keizers, Peter; van Riel, Antoinette; de Kaste, Dries
<x xml:space="preserve">Abstract</x> Food supplements are regularly found to contain pharmacologically active substances. Recently, the food supplement Dexaprine was removed from the Dutch market because it was associated with severe adverse events. Reports to the Dutch Poisons Information Center (DPIC) showed that ingestion of as little as half a tablet caused several cases of nausea, agitation, tachycardia, and palpitations and even one case of cardiac arrest. The remaining tablets of four patients were sent in by different healthcare professionals. Analysis by ultra‐performance liquid chromatography quadrupole time of flight mass‐spectrometry (UPLC–QTOF‐MS) confirmed the presence of synephrine, oxilofrine, deterenol, yohimbine, caffeine, and theophylline. Two more compounds were found which were tentatively identified as β‐methyl‐β‐phenylethylamines. This incident is only the next in a series of similar incidents involving dietary supplements with (undeclared) active substances that are either unsafe or have no known safety profile. Copyright © 2014 John Wiley & Sons, Ltd.